P-066 ABDOMINAL WALL RECONSTRUCTION FOLLOWING FULL THICKNESS BILATERAL RUPTURE OF THE RECTUS ABDOMINIS. (13th October 2022) - Suhail, D; Smith, O; Lim, P; Chintapatla, S
Abstract: Introduction: Rupture of the rectus abdominis is rare injury with no consensus on management. Previous reported cases have been due to exercise-related injuries and blunt abdominal trauma. We report the case of a 20-year-old male trainee paratrooper who presented with severe lower abdominal pain that occurred during military training. MRI revealed full-thickness bilateral rupture of the rectus abdominis. Abdominal wall reconstruction involved bilateral rectus muscle repair and placement of a biosynthetic mesh in the retrorectus plane. Postoperatively, our patient could walk pain-free at 3 weeks, jog pain-free at 10 weeks, and run up to 2 miles at 25 weeks. Methods: Pubmed, Medline and Embase were searched to identify relevant studies using the MeSH terms, "rectus abdominis" and "rupture", as well as their free text counterparts and synonyms. Texts were restricted to publications in English and publications after the year 2000. The search resulted in 391 articles. Manual cross-referencing was performed, limiting the included articles to 8 for review. Results: 6 out of the 8 selected articles discussed management using conservative means, while only 2 cases were managed surgically. Interestingly, no other exercise-related cases in the literature were managed surgically. Instead, all exercise related cases were managed conservatively, while only cases of traumatic aetiology were managed surgically. Among both surgically and conservatively treated patients, none suffered any treatment related complications, and all patients returned to normal levels of activity. Conclusion: Full-thickness, bilateral rupture of the rectus abdominis can occur during exercise. Surgical and conservative treatment yield similar results.